Development of a model safety in Egypt - Биссиуни, Радван Арафа (Proceedings of National Aviation University (archive), 2008)
The questions of related to development model of development of safety of labour are considered. The structure of mechanism of creation of normative document on a labour protection in Egypt is offered.